More Than the Rules: Using Pleading Drafting to Develop Lawyering and Transferable Skills - Katherine Curnow (Legal Education Review)
This paper discusses the development of an animal law case book, as part of an elective subject, “Animal Law and Policy in Australia”. The project was funded by a Vice-Chancellor’s Learning Grant, at UTS as well as a grant from the Animal Protection Institute, Voiceless. The project aimed at providing students with a meaningful learning experience that was consistent with the UTS Model of Learning and the graduate attributes established by the Faculty of Law and targeted practice-oriented learning and public service. The project was additionally prompted by the fact that no animal law case book is available in Australia. As such, it provides an example of an innovation in learning and teaching, demonstrating how practice-oriented learning in an emerging area of legal scholarship can potentially make a meaningful contribution to the field of study.